Il ritratto - Caroli, Flavio (Roma : Galleria La Salita, 1980)
Barni, Roberto ; Catalano, Elisabetta ; Abate, Alberto ; Boetti, Alighiero ; Dragomirescu, Radu ; Benveduti, Maurizio ; Catalano, Tullio ; Ceroli, Mario ; Galliani, Omar ; Clemente, Francesco ; Chia, Sandro ; Fioroni, Giosetta ; Germana, Mimmo ; Mariani, Carlo Maria ; Levini, Felice ; Mondino, Aldo ; etc.
Il ritratto, Galleria La Salita, Roma, 17 dicembre 1980
boek